2017
DOI: 10.3390/rs9111088
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of RISAT-1 and Radarsat-2 for Sea Ice Observations from a Hybrid-Polarity Perspective

Abstract: Utilizing several Synthetic Aperture Radar (SAR) missions will provide a data set with higher temporal resolution. It is of great importance to understand the difference between various available sensors and polarization modes and to consider how to homogenize the data sets for a following combined analysis. In this study, a uniform and consistent analysis across different SAR missions is carried out. Three pairs of overlapping hybrid-and full-polarimetric C-band SAR scenes from the Radar Imaging Satellite-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
1
20
1
Order By: Relevance
“…We note that in our study the σ 0 RV and σ 0 RH backscattering from FYI is much lower than the reported in [26]. The difference in FYI backscattering between the two studies should be related to the different environmental conditions, where in our study smooth thick FYI in dry winter conditions is investigated while in [26] wet or covered with fresh snow layer FYI was investigated during the melt season. Most of the FYI and MYI histograms in the investigated CP parameters do not conform to the normal distribution ( Figure 3).…”
Section: Histogram Analysiscontrasting
confidence: 60%
See 2 more Smart Citations
“…We note that in our study the σ 0 RV and σ 0 RH backscattering from FYI is much lower than the reported in [26]. The difference in FYI backscattering between the two studies should be related to the different environmental conditions, where in our study smooth thick FYI in dry winter conditions is investigated while in [26] wet or covered with fresh snow layer FYI was investigated during the melt season. Most of the FYI and MYI histograms in the investigated CP parameters do not conform to the normal distribution ( Figure 3).…”
Section: Histogram Analysiscontrasting
confidence: 60%
“…Results of this study showed that the second element of the Stokes vector, the right co-polarized ratio and the α s angle are three CP parameters that can be affected by a possible non-circularity of the transmitted radar signal from a CP SAR system. On the other hand, [26] found that the first element of the Stokes vector and the σ 0 RH (right-circular transmit and linear horizontal receive) and σ 0 RR (right-circular transmit and receive) backscattering coefficients are the best CP parameters for the separability between various sea ice types. These findings are also consistent with those reported earlier in [4] for simulated CP data, but for dry ice winter conditions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ponnurangam showed that, for soil moisture applications, HCP "works well" [59], and Uppala [60] found that compact polarimetry "works well" for maize crop discrimination. Espeseth et al [61] achieved "similar results" when comparing classifications derived from RISAT-1 HCP data and HCP data emulated from Radarsat-2 for sea ice applications. Kumar et al [62] applied unsupervised model-based classification techniques on the Stokes parameters from the RISAT-1 HCP mode to yield "very good" results.…”
Section: Results From Risat-1 Hcp Datamentioning
confidence: 72%
“…Relative phase (δ) ranges between −180 • and 180 • [12] and indicates that whether the surface (δ > 0) or double-bounce (δ < 0) scattering is dominant [27]. Similar to the alpha angle of Cloude-Pottier decomposition, Cloud α s [28] characterizes dominant scattering mechanism [29].…”
Section: Simulated Sar Datamentioning
confidence: 99%